2020
DOI: 10.1098/rstb.2019.0258
|View full text |Cite
|
Sign up to set email alerts
|

Human olfactory communication: current challenges and future prospects

Abstract: Although anthropologists frequently report the centrality of odours in the daily lives and cultural beliefs of many small-scale communities, Western scholars have historically considered the sense of smell as minimally involved in human communication. Here, we suggest that the origin and persistence of this latter view might be a consequence of the fact that most research is conducted on participants from Western societies who, collectively, were rather old (adults), deodori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 84 publications
0
37
0
3
Order By: Relevance
“…Although initially useful, this gender uniformity adds a constraint on generality, and the same goes for the almost exclusive reliance on participants that are Western, Educated, Industrialized, Rich, Democratic (WEIRD; Henrich et al, 2010) (cf. de Groot et al, 2018;Roberts et al, 2020). Generalizing research findings from WEIRD samples to other populations is a major problem in science in general, and a particularly pressing issue when one examines the breadth and scale of the non-verbal language of smells (Box 2).…”
Section: Problem I: Small Scale Slow Speedmentioning
confidence: 99%
See 2 more Smart Citations
“…Although initially useful, this gender uniformity adds a constraint on generality, and the same goes for the almost exclusive reliance on participants that are Western, Educated, Industrialized, Rich, Democratic (WEIRD; Henrich et al, 2010) (cf. de Groot et al, 2018;Roberts et al, 2020). Generalizing research findings from WEIRD samples to other populations is a major problem in science in general, and a particularly pressing issue when one examines the breadth and scale of the non-verbal language of smells (Box 2).…”
Section: Problem I: Small Scale Slow Speedmentioning
confidence: 99%
“…In our everyday lives, smells have a "communicative" function, informing us about the quality of food and warning us for environmental hazards (e.g., gas leaks) (Stevenson, 2010). An even less well-known function of smell is social communication (de Groot et al, 2017;Parma et al, 2017;Pause, 2017;Roberts et al, 2020); the topic of this article. Studies have shown that our smells provide others with cues about our identity and gender (Penn et al, 2007), age (Mitro et al, 2012), health (Olsson et al, 2014), and emotions (de Groot et al, 2015;Pause et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer all these questions will involve a substantial collective research effort, requiring attention from researchers with diverse areas of expertise who, ideally, will collect data from diverse segments of the human population (Roberts, Havlícˇek, & Schaal, 2020). This kind of research is rarely cheap or easy, which can pose a practical barrier to researchers with limited resources (and, even when resources are available, may be a disincentive within a scientific community that prizes large sample sizes).…”
Section: Future Directionsmentioning
confidence: 99%
“…This ability is present in micro-organisms as well as in complex species such as mammals. However, during evolution, human beings’ increasing reliance of other senses, such as vision, has decreased our sense of smell [ 2 ]. Nevertheless, the OS is the designated machinery for recognizing and elaborating conscious olfactory stimuli allowing humans to discriminate more than a trillion odorant stimuli [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%